2016
DOI: 10.3892/ijo.2016.3776
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated cell cycle progression of human regulatory T cell-like cell line caused by continuous exposure to asbestos fibers

Abstract: Asbestos exposure causes malignant tumors such as lung cancer and malignant mesothelioma. Based on our hypothesis in which continuous exposure to asbestos of immune cells cause reduction of antitumor immunity, the decrease of natural killer cell killing activity with reduction of NKp46 activating receptor expression, inhibition of cytotoxic T cell clonal expansion, reduced CXCR3 chemokine receptor expression and production of interferon-γ production in CD4+ T cells were reported using cell line models, freshly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
(68 reference statements)
1
15
0
Order By: Relevance
“…FoxO1 acts by regulating cell cycle-related genes, with negative regulation for accelerating cyclins and positive regulation for breaking cyclin-dependent kinase-inhibitors (CDK-Is). Thus, all sublines showed increased expression of cyclins and decreased expression of CDK-Is which resulted in the acceleration of cell cycle progression (31). These findings indicate that asbestos exposure induces enhanced Treg function as well as proliferation.…”
Section: Aberrant Expression Of Foxp3 In a Human T Cell Line Possessimentioning
confidence: 73%
“…FoxO1 acts by regulating cell cycle-related genes, with negative regulation for accelerating cyclins and positive regulation for breaking cyclin-dependent kinase-inhibitors (CDK-Is). Thus, all sublines showed increased expression of cyclins and decreased expression of CDK-Is which resulted in the acceleration of cell cycle progression (31). These findings indicate that asbestos exposure induces enhanced Treg function as well as proliferation.…”
Section: Aberrant Expression Of Foxp3 In a Human T Cell Line Possessimentioning
confidence: 73%
“…In addition, in cell cycle phase analysis, subline showed higher S/G1 ratio (S-phase% was divided with G1 phase%) than that of original line. In addition, knockdown of FoxO1 in subline using siRNA induced increased expression of cyclin D1, the most enhanced expression in subline [54]. These results indicated that reduced FoxO1 caused by asbestos exposure induced enhancement of cell cycle progression.…”
Section: The Effects Of Silica and Asbestos On Treg Silica Induces Ementioning
confidence: 76%
“…For example, as previously reported, continuous exposure of the human NK cell line YT-A1 to chrysotile asbestos for more than five months resulted in reduced antitumor killing activity against the human erythroblastic leukemia cell line K562, a commonly used target cell line to assay NK cell activity and compared with the original YT-A1 cell line, which has never been exposed to asbestos fibers (7-9). Regarding our previous reports showing that asbestos fibers enhance Treg function (43) and increase its volume by acceleration of the cell cycle (44), the construction of a cell co-culture model using human cell lines such as a Treg cell model or responder T cell model with mesothelioma (or other cancer) model might be difficult. As we previously reported, subjecting a human Treg model comprising the MT-2 cell line to continuous exposure to asbestos resulted in increased production of IL-10 and TGFβ (43).…”
Section: Discussionmentioning
confidence: 99%